STAD TECHNIQUE IN TEACHING READING TO THE EIGHTH GRADERS OF SMPN 50 SURABAYA - RATNA SARI, AJENG (RETAIN : Journal of Research in English Language Teaching, 2015)
Abstract Junior High School students are expected to be able to read and understand narrative and descriptive text well (BSNP, 2013). Based on the researcher experience, the researcher found that one English teacher in SMPN 50 Surabaya used STAD technique in teaching reading. The previous studies about STAD implementation had been done but none of them had discussed whether the implementation followed the procedure of STAD or not and whether there were some obstacles in the implementation of STAD. For this reason, the researcher conducted a research about the investigation of STAD technique into the practice and the obstacles that teacher faced in the practice. This research was a case study. The data for this research was collected using observation sheet, field note and tape recording. The researcher coded the data and categorize into STAD procedure and obstacles then researcher made conclusion from the code and categorization. The findings showed that teacher followed the STAD procedure suggested by Slavin (1994), but there were some differences in the implementation. The differences were in quiz and team recognition. The quiz had to be done after two or three times meetings, but the finding showed that teacher only did a meeting and she gave the quiz in that meeting. The other difference was in team recognition the teacher did not compare the current score with the previous score. Teacher also faced some obstacles in implementing STAD technique. The obstacles included teacher’s two languages use, the students being too active, and not getting quiet. Teacher also found that some students fell asleep in the classroom. The difficulty in the seats arrangement also became the obstacle for the teacher. All those obstacles pursued the teaching learning efficiency. Keywords: STAD Technique, teaching reading, the obstacles Abstrak Murid-murid Sekolah Menengah Pertama diharapkan mampu membaca dan memahami teks naratif dan deskriptif dengan baik (BSNP,2013). Berdasarkan pengalaman, peneliti menemukan bahwa salah seorang guru Bahasa Inggris di SMPN 50 Surabaya menggunakan STAD tehnik dalam mengajar membaca. Penelitian-penelitian sebelumnya tentang penerapan STAD telah dilakukan namun tidak satupun membahas apakah penerapan tersebut mengikuti prosedur STAD atau tidak dan apakah ada beberapa kendala-kendala dalam penerapam STAD. Oleh karena itu, peneliti melakukan sebuah penelitian tentang investigasi STAD tehnik dan kendala-kednala yang dihadapi guru dalam penerapannya. Penelitian ini merupakan studi kasus. Data dalam penelitian ini dikumpulkan menggunakan lembar observasi, catatan penelitian dan alat perekam. Peneliti mengkodekan data dan mengkategorikannya menjadi prosedure STAD, dn kendala-kendala yang dihadapi guru kemudian peneliti membuat kesimpulan dari pengkodean dan pengkategorian tersebut. Peneliti mneemukan bahwa guru tersebut mengikuti prosedure STAD yang diusulkan oleh Slavin (1994), tetapi ada beberapa perbedaan dalam penerapannya. Perbedaannya yaitu dalam quiz dan team recognition. Quiz seharusnya dilakukan setelah dua atau tiga kali pertemuan, tetapi dalam kenyataannya menunjukkan bahwa guru tersebut hanya melakukan satu kali pertemuan dan dia memberikan quiz pada pertemuan tersebut. Perbedaan yang lain yaitu dalam team recognition, guru tersebut tidak membandingkan nilai yang didapat saat ini dengan nilai sebelumnya. Guru juga menghadapi beberapa kendala dalam penerapan STAD tehnik. Kendala-kendala tersebut yaitu guru harus menggunakan dua bahasa (Bahasa Indonesia dan Bahasa Inggris) di dalam kelas dan murid-murid juga terlalu aktif dan tidak bisa diam. Guru juga mendapati beberapa murid tertidur di dalam kelas. Kesulitan dalam penataan tempat duduk juga menjadi halangan untuk guru. Semua halangan-halangan ini mengganggu efisiensi belajar mengajar. Kata Kunci: STAD Tehnik, pengajaran membaca, kendala-kendala